2018
DOI: 10.1055/s-0037-1613716
|View full text |Cite
|
Sign up to set email alerts
|

Periosteal Graft Myringoplasty: Our Experience

Abstract: Introduction  Different types of autologous graft materials are used for myringoplasty, with the temporalis fascia and cartilage being the most frequently used tissues. Periosteal tissue has been used for a long time in our department, and many advantages support its use in myringoplasty. To the best of our knowledge, this issue is scarcely discussed in the previously published literature. Objective  To present our experience with periosteal graft myringoplasty, describing the technique and the anatomical and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 9 publications
1
4
0
1
Order By: Relevance
“…7,8,12 Proper selection of a suitable graft is crucial, especially in pediatrics, due to recurrent episodes of respiratory tract infection, which threaten surgical success. 9 Our results have shown an excellent graft uptake (95%), which are similar to those observed by ElTaher et al 7 (93%), Rao et al 8 (96%) Elmoursy and Elbahrawy 12 (95%), and ElBatawi et al 13 (93%). These results are also comparable to those found for other types of grafts, whether temporalis fascia or cartilage grafts.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…7,8,12 Proper selection of a suitable graft is crucial, especially in pediatrics, due to recurrent episodes of respiratory tract infection, which threaten surgical success. 9 Our results have shown an excellent graft uptake (95%), which are similar to those observed by ElTaher et al 7 (93%), Rao et al 8 (96%) Elmoursy and Elbahrawy 12 (95%), and ElBatawi et al 13 (93%). These results are also comparable to those found for other types of grafts, whether temporalis fascia or cartilage grafts.…”
Section: Discussionmentioning
confidence: 99%
“…8 To the best of our knowledge, the mentions of the use of the periosteum in pediatric CSOM in previous research are scarce. Some authors have reported 7,8,12 their experience with periosteal myringoplasty, but not in patients in a specific age group. In addition, most of their study samples were composed of adults.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…В литературе также встречаются единичные сообщения об использовании других соединительнотканных аутотрансплантатов, в том числе широкой фасции бедра, венозной стенки, периоста, использование которых не нашло широкого применения в тимпанопластике [14][15][16].…”
Section: история вопросаunclassified